A survey of the Public Administration Library collection of eleven ASAP member schools in Metro Manila - Pantola, Alicia T. 1945-
Based on these findings, some conclusions were drawn: 1) the amount of library fees, source of library funds and percentage of the total book fund alloted for the acquisition of public administration materials influence the growth of the collection; 2) some library heads have no professional qualification in the field of library science; 3) awareness of the field of public administration affects the extent of public adminstration collection by subject-area as familiarity with the public administration sub-fields provides the librarian a basis for acquisition; 4) the number of years of the school establishment somehow indicate the extent of the collection in terms of volume as illustrated in the case of UP CPA and Greenville College which are the oldest and the youngest public administration schools in the country, respectively; 5) the number of modes applied in acquiring and manner of ordering affect the volume generated by the library.